Integrating IoT and Blockchain for Enhanced Security: Challenges and Solutions - Ahmad Anwar bin Zainuddin; Aina Syazana binti Mortadza; Faheyra Ezzah binti Musa (PT. Visi Media Network, 2024)
The integration of Internet of Things (IoT) and blockchain integration addresses security concerns in IoT devices through decentralized networks. Challenges include scalability, interoperability, and privacy. Proposed solutions involve decision frameworks, lightweight consensus mechanisms, and hybrid architectures. Smart contracts and privacy-preserving techniques enhance secure transactions. Integration benefits industries like healthcare, supply chain, and energy by improving efficiency and transparency. The methodology involves selecting a blockchain platform, designing a consensus mechanism, developing smart contracts, and integrating IoT devices. Challenges like data ownership and governance can be mitigated through policies and privacy-preserving techniques, ultimately optimizing operations, and improving customer satisfaction across industries.